Understanding community actions in environmental education in Chiquinquirá, Boyacá - Figueroa-Vargas, Deisy; García-García, Luz Elena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The article presents the results of the research that aimed to know the perceptions about the community actions done in environmental education in the municipality of Chiquinquirá, Boyacá, Colombia. The approach was the hermeneutic with an interpretative method. The techniques for the collection of information were dialogic encounters and focused interviews. They were implemented with environmental and community leaders, experts in the region, teachers and students. The results showed actions of reorientation of values such as: respect for nature and life, preservation and environmental protection, rational use of natural resources and social responsibility with cultural sense. The school environmental projects include the environmental dimension, but require an understanding of the local community and institutional appropriation, as well as a response to the community dynamics. Actions such as reforestation, reduction of garbage volumes, and cleaning river shores demand of the inhabitants a greater awareness, change of pedagogical strategies and reorientation of environmental knowledge. There is a need of training environmentally committed citizens in order to reduce the decay of nature.